A STUDY ON PATIENTS AWARENESS ON RATIONAL USE OF ANTIBIOTICS AND ITS RESISTANCE - Maheshwari P; D, Praveen; V, Ravichandiran (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: Antibiotics are needed for many serious illnesses such as bacterial pneumonia, bacterial meningitis, septicemia, and even strep throat. These illnesses can be life threatening or can lead to serious complications. The work aims to create an awareness on antibiotics and its resistance in patients. The main objective of this work is to study the patient knowledge through knowledge assessment questionnaire, to promote the rational use of antibiotics and to educate the patients using antibiotics. Methods: A questionnaire was prepared and data were collected from the patients based on which the study was carried out. Results and Conclusion: A very high consumption of antibiotics was observed.there was a higher use of cephalosporins. Dispensing of antibiotics is very high in community pharmacy despite of federal regulations, heath education programs should be taken to the patients regarding antibiotics. Keywords: Rational use, Antibiotics, Resistance.